How does a reformed course look after many years? A case study of the reformed calculus-based introductory physics course at KSU. - Budhathoki, Santosh (Kansas State University, 2019)
We studied what happened after the reform, of the first semester, calculus-based introductory physics course, that took place almost 20 years ago. We examined how the physical environment, curriculum, the method of instruction, and the learning gain as measured by the FCI have changed over time since the reform. The system that was put in place by the originators of the reform seems to be self-sustaining because the overall structure of the reform has remained largely intact. The course content and the lab experiments have remained almost the same. However, some minor modifications such as the introduction of the cooperative group problem-solving and the use of online homework are being used by some lead instructors teaching this course. The graduate students are introduced as primary instructors, LAs are being used as the secondary assistants in the studio, and clickers questions are being used in the lectures. The FCI was used to assess the learning gain of the students and the success of the initial reform. The data show that the learning gain was higher immediately after the reform but has dropped more than a decade later. The focus of the research has been to explore the reasons for the fall in the learning gain in later semesters. Knowing why it dropped would give us information about how to sustain future reforms. We show that our data is reliable and use it to eliminate several possible explanations for the drop in the learning gain. For future study, one may look at the amount of time faculty spend thinking about teaching and how that changes over time as a measure of ``investment" in the course. One can also study how the group formation in the studio affects the learning gain. One may also take videos of the lectures and the studios and analyze them to see how is the distribution of time for the quiz/CGPS, lab experiment and the review of the homework problems in each studio, how much do the students actually get the opportunities to engage in active learning, how much do each students in a cooperative group contribute in learning. All these detail video analyses can provide answers to the changes in the learning gain if there is any in the future.
Keywords: Course reform